Interest rates, promotional prizes and competition in the banking industry (2003)
Some Colombian commercial banks have used the strategy of offering promotional prizes in order to attract new savings customers. In this paper we develop a two-stage game model that allows us to understand the effects of this promotional strategy on the deposit interest rates, the deposit market shares and the intermediation spreads.We find that under this strategy it is possible for the bank that offers the highest prize to segment the deposit market serving only customers that assign high subjective probabilities to winning prizes. More importantly we show that the bank that offers the highest promotional prize not only pays the lowest deposit interest rate but also has the largest deposit market share and the widest intermediation spread